FEATURES OF SUBSTRATES FORMATION FOR X-RAY RADIATION SENSOR - I. V. Gasenkova; G. A. Vlasova; E. E. Kolesnik; M. V. Yasin (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The design and technological features of the formation of substrates with a periodic system of microsensors for the construction of radiation is described. Series of operations to create such substrates by anodic alumina are shown.